2010
DOI: 10.1190/1.3494083
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear extended images via image-domain interferometry

Abstract: Wave-equation, finite-frequency imaging and inversion still face many challenges in addressing the inversion of highly complex velocity models as well as in dealing with nonlinear imaging ͑e.g., migration of multiples, amplitude-preserving migration͒. Extended images ͑EIs͒ are particularly important for designing image-domain objective functions aimed at addressing standing issues in seismic imaging, such as two-way migration velocity inversion or imaging/inversion using multiples. General oneand two-way repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 76 publications
0
63
0
Order By: Relevance
“…Interferometry by multidimensional deconvolution as such can be compared with migration deconvolution (Hu et al, 2001;Yu et al, 2006;Zhang and Ulrych, 2010). Such an analogy is also pointed out by Vasconcelos et al (2010), who present an imaging condition for oneway wavefields that is very similar to equation 4. In migration, the PSF generally has to be obtained from a velocity model, whereas in interferometry it can be computed from actually measured Green's functions, allowing us to focus not only the direct arrival but instead focus the complete wavefield.…”
Section: Discussionmentioning
confidence: 81%
“…Interferometry by multidimensional deconvolution as such can be compared with migration deconvolution (Hu et al, 2001;Yu et al, 2006;Zhang and Ulrych, 2010). Such an analogy is also pointed out by Vasconcelos et al (2010), who present an imaging condition for oneway wavefields that is very similar to equation 4. In migration, the PSF generally has to be obtained from a velocity model, whereas in interferometry it can be computed from actually measured Green's functions, allowing us to focus not only the direct arrival but instead focus the complete wavefield.…”
Section: Discussionmentioning
confidence: 81%
“…Retrieved from surface seismic data, extended images (EIs) can be thought of as local reflectivity responses of the subsurface, for pseudo-sources and receivers placed inside of the medium (Vasconcelos et al, 2010;Thomson et al, 2016). Here, we further extend this concept by defining the block system , (1) where the quantities involved are (Figure 1) , (2) (3) and (4).…”
Section: Target-enclosing Extended Images (Teeis) and Marchenko-redatmentioning
confidence: 99%
“…1b), with pseudosources both on the top (denoted by R + and T + ) and bottom (Rand T -). In equation 1, the TEEIs are properties of the enclosed medium that take the input F in fields into the output F out : the matrix blocks P + and P -are, respectively, down-and up-going wavefield matrices (Vasconcelos et al, 2010;van der Neut et al, 2013) due to sources on the acquisition surface, observed either on the top or bottom datums, as indicated by the subscripts top and bot (Fig. 1a).…”
Section: Target-enclosing Extended Images (Teeis) and Marchenko-redatmentioning
confidence: 99%
See 1 more Smart Citation
“…By propagating wavefields backward in a detailed subsurface model, rather than in a smooth macro model, and crosscorrelating them with their associated source fields in the detailed model, we can image the primary reflections and internal multiples to improve seismic resolution (Youn and Zhou, 2001;Malcolm et al, 2009;Vasconcelos et al, 2010). Because internal multiples are used in this image, this strategy has also been referred to as nonlinear imaging (Fleury and Vasconcelos, 2012;Ravasi et al, 2014).…”
Section: Target-enclosed Imagingmentioning
confidence: 99%